Contribution to the knowledge of threatened Mexican cacti - Hernandez, Hector M.; Godinez A., Hector (Instituto de Ecología, A.C., 1994)
Mexico is the most important center of concentration of genera and species of cacti, most of which are endemic (73 and 78% respectively). Most of the species occur in the arid or semiarid regions of the country, especially in the southeastern portion of the Chihuahuan Desert, including the Queretaro-Hidalgo Arid Zone.  Many of the species are under collecting pressures and their habitats are being destroyed. In addition, these have a limited ability to reestablish demographically after a disturbance event.  Consequently, a significant number of mexican cacti are listed as endangered.